2020
DOI: 10.3389/fonc.2020.00548
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Human Papillomavirus Vaccination for Persistence of Immunity for Cervical Cancer Prevention: A Critical Review With Experts' Opinions

Abstract: The development of cervical cancer has been shown to involve both viral and host factors. The host factors are those that determine the specific response to human papillomavirus (HPV) infection by the patient's immune system. The immune responses to vaccines have been shown to be influenced by polymorphisms in genes involved in innate and adaptive immunity. The specific genetic variants that may influence the immune responses to HPV vaccine which may contribute to persistence of immunity (POI) have not been wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…However, in stark contrast to the global data, we report here a >13-fold higher frequency (26%) of HPV35 among Zimbabwean women with cervical cancer, compared to Caucasians (~2%) and Asian (~1%) cervical cancer patients [ 48 , 49 ]. Across the African continent, there is heterogeneity in the frequency of HPV35, ranging from as low as 6% in South Africa, Burkina Faso (9%), Nigeria (9%), Tanzania (15%), Mozambique (17%), and up to the comparable 24% observed among Malawian women [ 18 , 28 , 50 58 ]. It is important to note, an earlier study among Zimbabwean women [ 22 ] which showed a frequency of 11% for HPV35.…”
Section: Discussionmentioning
confidence: 99%
“…However, in stark contrast to the global data, we report here a >13-fold higher frequency (26%) of HPV35 among Zimbabwean women with cervical cancer, compared to Caucasians (~2%) and Asian (~1%) cervical cancer patients [ 48 , 49 ]. Across the African continent, there is heterogeneity in the frequency of HPV35, ranging from as low as 6% in South Africa, Burkina Faso (9%), Nigeria (9%), Tanzania (15%), Mozambique (17%), and up to the comparable 24% observed among Malawian women [ 18 , 28 , 50 58 ]. It is important to note, an earlier study among Zimbabwean women [ 22 ] which showed a frequency of 11% for HPV35.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical carcinoma is a major cancer affecting women's health and one of the highest rates of cancer‐related deaths in developing countries 1 . The pathogenesis of cervical carcinoma has been proven to be related to HPV virus infection and patient immune degradation 2 . However, to date, no antiviral drugs that are effective in eliminating HPV have been identified.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The pathogenesis of cervical carcinoma has been proven to be related to HPV virus infection and patient immune degradation. 2 However, to date, no antiviral drugs that are effective in eliminating HPV have been identified. The blocking and self‐clearing of local cervical HPV infection depend on the state of the host's immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while there is a possible occurrence of adverse effects after HPV vaccination, these results do not necessarily signal the negation of the usefulness of this vaccine for the prevention of uterine cervical cancer [ 41 ]. If the information reported in this study is provided and is widely available at the induction of HPV vaccines, a social distaste for HPV vaccination (All Japan Coordinating Association of HPV Sufferers) would likely not occur in Japan.…”
Section: Discussionmentioning
confidence: 99%